Exploitation of filamentous and picoplanktonic cyanobacteria for cosmetic applications: potential to improve skin structure and preserve dermal matrix components - Morone, Janaína (2020)
The use of natural products in skin care formulations gained interest as a concern formodern societies. The undesirable side effects of synthetic compounds, as well as the associatedenvironmental hazards, have driven investigation on photosynthetic organisms as sustainable sourcesof effective and environmentally friendly ingredients. The use of natural extracts in cosmetics hasbeen highlighted and, along with plants and algae, cyanobacteria have come into focus. Due totheir low culture demands, high grow rates and ability to produce a wide variability of bioactivemetabolites, cyanobacteria emerged as an economic and sustainable base for the cosmetic industry.In this study, we evaluated the potential of ethanol extracts of picocyanobacteria strains of the generaCyanobiumandSynechocystis and filamentous strains of the generaNodosilinea,PhormidiumandTychonemafor skin applications, with focus in the field of anti-aging. The extracts were analyzedfor their pigment profile, phenolic content, antioxidant potential, cytotoxicity against keratinocytes(HaCat), fibroblasts (3T3L1), endothelial cells (hCMEC/D3) and capacity to inhibit hyaluronidase(HAase). The total carotenoid content ranged from 118.69 to 383.89μg g−1of dry biomass, and the totalphenolic content from 1.07 to 2.45 mg GAE g−1. Identified carotenoids consisted of zeaxanthin, lutein,canthaxanthin, echinenone andβ-carotene, with zeaxanthin and lutein being the most representative(49.82 and 79.08μg g−1, respectively). The highest antioxidant potential was found forPhormidiumsp.LEGE 05292 andTychonemasp. LEGE 07196 for superoxide anion radical (O2•−) scavenging (IC50of822.70 and 924μg mL−1, respectively). Low or no cytotoxicity were registered. Regarding HAaseinhibition,Tychonemasp. LEGE 07196 andCyanobiumsp. LEGE 07175 showed the best IC50(182.74and 208.36μg mL−1, respectively). In addition, an increase in fibroblast proliferation was registeredwith these same strains. From this work, the ethanol extracts of the speciesTychonemasp. andCyanobiumsp. are particularly interesting for their potential application in anti-aging formulations,once they stimulated fibroblast proliferation and inhibit hyaluronic acid digestion.